IMPLEMENTASI PENCANANGAN KEBIJAKAN KAWASAN BEBAS KUMUH MELALUI HUNIAN MODEL RUSUNAWA (Rumah Susun Sederhana Sewa) DI KOTA PEKALONGAN - Siti As'adah Hijriwati; Siti Zulaekhah (LPPM Universitas Pekalongan, 2012)
Abstract This research aims to analyze the implementation of rural house complex policy, especially strata tittle, in order word condominium, in Pekalongan City. These policy has been implemented in order to fasilitate the minimum necessities of rural housing. There are some problems in this research. First,how does the implementation of the rural housing complex, condominium policy in Pekalongan City? Second, what problems are occured because of this policy?This research typically descriptive-analyze. We want to describe all of local government policy in rural house complex as condominium then analize them until results the real conclusion. In order to describe all, socio legal method has been used. The rules of these policy can not be seen unless knowing it’s implementation in the real human being life. All data, both primary and secondary also supported to dig out many problems of crude worker, especially sailormen in north beach of Pekalongan Residence. Data searched by documentary for secondary data and interview for primary data in other side. This research concludes that there are some problems in the exsistence of this rural house complex in vertical building named ”Rusunawa”, a simple housing complex with the rent system. Legal problem shows in uncertainty of the occupation. Some of them escapes from Rusunawa before they pay the rent cost. Keywords: rural housing complexs, rusunawa, condominium